PENGELOLAAN AIR LIMBAH DOMESTIK DI DKI JAKARTA - Said, Nusa Idaman (Center for Environmental Technology, 2006)
Water pollution problem caused by household waste water in the region of DKI Jakarta, and more made worse by affecting of expanding settlement area in buffer zone around Jakarta which without provided with waste water facilities, so that all waste water thrown to public channel and finally flowing Ã‚Â into river bodies in region of DKI Jakarta.To overcome the mentioned above Government of Province DKI Jakarta have released Regulation of Governor Province Special District Capital of Jakarta Number 122 Year 2005 About Management Of Domestic Water Waste In Province Special District Capital Of Jakarta.Ã‚Â According To Regulation Of Governor of DKI Jakarta Number 122 Year 2005 Section 7 express that house building and non house building is obliged to manage domestic waste water before discharge to public channel or drainage.Ã‚Â Planning of domestic waste water treatment installation which represent environmental utilities or building represent conditions in course of publication of Permit Directing Of Usage Of Land;Ground (SIPPT), Plan Arrange Situation Building ( RTLB), Permission Found Building (IMB), and awaking up of domestic waste water treatment installation represent conditions in course of publication of Permit of Building Usage (IPB) and Elegibility Use Building (KMB), and also licensing of operational of institution in charge related to such operational.Ã‚Â Ã‚Â Kata Kunci : Air limbah domestik, air limbah rumah tangga, pengelolaan.